On the existence of positive solutions of a class of parabolic reaction diffusion systems - REDJOUH, Mounir; MESBAHI, Salim (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper, we show the existence of continuous positive solutions of a class of nonlinear parabolic reaction diffusion systems with initial conditions using techniques of functional analysis and potential analysis. Mathematics Subject Classification (2010): 34B27, 35B09, 35K41, 35K57. Received 18 October 2019; Accepted 17 January 2020.